Production Cost Structure and Profit In The Plastic Industry For Packaging In Indonesia - Yuzak Afan Faqih; Deassy Apriani; Ichsan Hamidi (UNIVED Press, 2025)
The plastics for packaging industry play an important role in the Indonesian economy. The plastic industry for packaging has experienced relatively high growth along with the growth of the food and beverage sector, pharmaceuticals, cosmetics, and other industries. This study aims to determine and analyze the effect of production cost structure on the profit of the plastic industry for packaging in Indonesia. This study uses secondary data in the form of Time Series from the Indonesian Statistics for the period 1991-2021. The analysis technique used in this research is descriptive quantitative analysis technique. The analysis method used is the calculation of production cost structure, calculation of profit level and multiple linear regression (Ordinary Least Square). The results showed that the production cost structure has experienced significant development, the cost of raw materials is the highest composition of production costs with a percentage of 82.29 percent. The profit of the plastic industry for packaging has grown by 20.75 percent per year. Results of multiple linear regression, the production cost structure has a significant effect on profits, but the capital cost variable does not have a significant effect on in the plastic industry for packaging in Indonesia. The negative coefficient on the capital cost and energy cost variables means that there has been a saving in the use of capital and energy.